Specialised Dictionaries of Economics and Translation - Fuertes-Olivera, Pedro A. (HERMES - Journal of Language and Communication in Business, 2013)
This article describes the “Dictionary of Economics” in terms of the Function Theory of Lexicography. It defends the thesis that such information tools must be designed for assisting specific users to solve the specific needs they have in a translation situation. In particular, I will focus on the solutions offered for individualising data retrieval, which will in turn eliminate the so-called information stress or information death produced when users retrieve so much data that they cannot cope with it. This process is illustrated in two recent online dictionaries, the Diccionario Inglés-Español de Contabilidad: Traducción (Fuertes-Olivera et al. 2012a) and the Diccionario Inglés-Español de Contabilidad: Traducción de Frases y Expresiones (Fuertes-Olivera et al. 2012b). They are especially suitable when translating English accounting texts into Spanish. These two dictionaries are considered high quality 21st Century dictionaries, e.g., as candidates for assisting in the training of professional translators within the field of Economics, one of the topics discussed in this Special Issue of Hermes.